Recent advances in 2D material-based phototherapy - Tan, Yi; Khan, Haider Mohammed; Sheikh, Bilal Ahmed; Sun, Huan; Zhang, Hui; Chen, Jie; Huang, Dingming; Chen, Xinmei; Zhou, Changchun; Sun, Jianxun (Frontiers in Bioengineering and Biotechnology, 2023)
Phototherapy, which generally refers to photothermal therapy (PTT) and photodynamic therapy (PDT), has received significant attention over the past few years since it is non-invasive, has effective selectivity, and has few side effects. As a result, it has become a promising alternative to traditional clinical treatments. At present, two-dimensional materials (2D materials) have proven to be at the forefront of the development of advanced nanomaterials due to their ultrathin structures and fascinating optical properties. As a result, much work has been put into developing phototherapy platforms based on 2D materials. This review summarizes the current developments in 2D materials beyond graphene for phototherapy, focusing on the novel approaches of PTT and PDT. New methods are being developed to go above and beyond conventional treatment to fully use the potential of 2D materials. Additionally, the efficacy of cutting-edge phototherapy is assessed, and the existing difficulties and future prospects of 2D materials for phototherapy are covered.